Conflict reporting: Emotional attachment, a sense of morality and reporting objectively - Janine Cohen (Asia Pacific Network, 2010)
This article explores how emotional attachment and a sense of morality often drive journalists to produce great work in areas of conflict, particularly those solo video journalists who produce long format current affairs. But it also questions if a sense of engagement can impede journalist’s ability to report objectively? And how relevant is this ideal today? Former BBC war correspondent Martin Bell changed his view on objectivity after covering the Balkans War. He advocated for a journalism of attachment especially in war zones and amid human suffering. There are some Australian video journalists whose sense of engagement has defined outstanding bodies of work. However, some practices in the field often defy concepts of impartiality. Issues of, if, or when, to put down the camera and give assistance; or how to remain fair and honest to the story while gaining the long term trust of sources, sometimes challenges journalists.